Smithells light metals handbook - Smithells, Colin J. (Colin James); Brandes, Eric A. (Eric Adolph); Brook, G. B. (Oxford [England] ; Boston : Butterworth-Heinemann, 1998)
'The Smithells Metals Reference Book' is one of the best known and most trusted sources of reference for the professional metallurgist or materials scientist, and has been so since its inception in 1949. Drawing upon the data contained within this respected work, and completely updating and revising it where necessary to bring the information completely up to date, the editors have created a new book which is dedicated to the most commonly used and popular light metals. 'The Smithells Light Metals Handbook', with its combination of comprehensive data on properties, standards and international materials specifications coupled with other unique features like the extensive section of binary phase diagrams, will no doubt become a standard reference work for the industrial and theoretical metallurgist. Containing all the data that you will ever need with respect to Aluminium, Magnesium and Titanium, this book will be an invaluable tool for anyone working in the design, manufacture or use of components or raw materials in these areas. THE standard reference work for metallurgists Contains all data for researchers and professional metallurgists Fully updated.
General physical and chemical constants; Metallography; Equilibrium diagrams; General physical properties; Mechanical testing; Mechanical properties of metals and alloys; Sintered materials; Casting alloys and foundry data; Heat treatment; Guide to corrosion control; Electroplating and metal finishing; Welding; Index.
Includes index.
Keywords: Light metals -- Metallurgy; Light metal alloys; Electronic books